Electron Transfer Mediators for Photoelectrochemical Cells Based on Cu(I) Metal Complexes - Michele Brugnati; Stefano Caramori; Silvia Cazzanti; Luca Marchini; Roberto Argazzi; Carlo A. Bignozzi (International Journal of Photoenergy)
The preparation and the photoelectrochemical characterization of a series of bipyridine and pyridyl-quinoline Cu(I) complexes, used as electron transfer mediators in regenerative photoelectrochemical cells, are reported. The best performing mediators produced maximum IPCEs of the order of 35–40%. The J-V curves recorded under monochromatic light showed that the selected Cu(I)/(II) couples generated higher Vocs and fill factors compared to an equivalent I-/I3- cell, due to a decreased dark current.